PELATIHAN STRATEGI SELF-REGULATED LEARNING FASE FORETHOUGHT UNTUK STUDENT ENGAGEMENT SISWA SMP - Aripin, Natania Alfega; Savitri, Jane; Megarini, Maria Yuni (Universitas Islam Indonesia, 2023)
Student engagement issues are commonly found in schools, particularly among junior high school students. One of the internal factors that can enhance student engagement is students' proficiency in utilizing self-regulated learning strategies during the forethought phase. SRL forethought was provided in the form of experiential training, where students learned through their own experiences. Participants in this research were 12 students in the control group and 11 students in the experimental group. The results of the difference test indicate that SRL forethought training is effective in improving student engagement in seventh-grade students (p=0.018; z=-2.358). The control group also demonstrated significant differences between pre and post-test conditions (p=0.40; z=-2.051). In conclusion, SRL forethought training is essential for students to prevent a decline in engagement in seventh-grade students. Subsequent researchers may conduct subject randomization based on student engagement categories to achieve a more balanced initial condition.